Failure Mechanism and Mitigation Measures of the G1002 Electricity Pylon Landslide at the Jinping I Hydropower Station - Gang Luo; Yutian Zhong; Yuanxiang Yang (Advances in Civil Engineering)
On August 29 and 30, 2012, local extreme rainfalls struck the construction area of the Jinping I Hydropower Station, Xichang, China, and triggered many geohazards. The upper region of the left valley slope 200 m downstream of the dam failed and slid, exposing the D-pile of the G1002 electricity pylon and threatening the entire power transmission line. Therefore, guaranteeing the stability of the residual soil masses in the rear area of the main scarp and the safety of the G1002 electricity pylon became a primary emergency task. Geological field surveys, topographical mapping, study of the failure mechanisms, and stability evaluations were carried out from October 12, 2012, to November 7, 2013. It is revealed that the failure mechanism of the G1002 electricity pylon landslide is flood-induced tractive sliding along the interlayer between the colluvium and the bedrock, significantly influenced by heavy precipitation and frequent blasting activities during the dam construction. The residual soil masses around the G1002 electricity pylon foundation are unstable under rainfall conditions. In order to ensure the stability of the residual soil masses and pylon foundation, a mitigation measure of the anchor cables combined with lattice frame beams was proposed and applied in practice. This paper provides insights into the problems associated with the selection of the locations of electricity pylons in ravine regions as well as mitigation strategies for similar landslides.